Handling Community Tensions During the Hajj Waiting Period: An Analysis of the Reactualization of Hajj Implementation - Abbas Sofwan Matlail Fajar; Akhmad Najibul Khairi Syaie (Tribakti: Jurnal Pemikiran Keislaman, 2023)
Hajj, a pillar of Islam for Muslims who are able, has a high spiritual dimension while involving social, economic, and psychological aspects in its preparation and execution. The waiting period before Hajj is often challenging, especially in the context of people's anxiety. This study aims to analyze and understand anxiety during the Hajj waiting period and its impact on the preparation and actualization of worship. In the context of the data type and research objectives, a non-positivistic or naturalism paradigm was used. Qualitative research, which focuses on human actions and interactions in natural settings, defines this approach. The research findings show that the frustration experienced by prospective pilgrims is not only influenced by the long waiting period and the additional costs required but also includes a deeper aspect of cosmological roots in Muslim understanding. Hajj, one of Islam's high pillars, has shifted people's perceptions to be more than just an achievement in the spiritual journey. However, it should be noted that this study needs to be more focused in its focus, which is on analyzing the queuing aspect of the waiting period. This study has yet to explore the regulation of Hajj worldwide, which has significant variations, including developing the nusuk application technology proposed by the Saudi Arabian government to address queuing issues.